Alveolar rhabdomyosarcoma of the neck in a two-months-old baby: diagnostic challenges - Nordashima Abd Shukor; Azyani Y; Amizatul Aini S; Boekhren KB; Pathmanathan R; Hamidah A (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Rhabdomyosarcoma (RMS) is the most common soft tissue malignancy in children and adolescents. The rarity of its occurrence in infant poses a great difficulty in terms of diagnosis and management. Here, we report an aggressive case of alveolar rhabdomyosarcoma in an infant who presented with neck swelling and neurological complications. The Magnetic Resonance Imaging (MRI) revealed a soft tissue swelling of the neck with intraspinal extension and spinal cord compression, raising the possibility of a neurogenic or malignant nerve sheath tumour. Histopathological examination revealed a primitive, small round cell tumour with no rhabdoid differentiation. The clinical presentation, neurological symptoms, tumor location and the histopathologic features were highly suggestive of neuroblastoma. However, the tumour cells were positive for desmin with focal and weak nuclear positivity for myogenin and MyoD1; immunoexpressions which were in favour of rhabdomyosarcoma. Fluorescent in situ hybridization (FISH) confirmed the presence of a translocation t(2;13)(q35;q14), supporting the diagnosis of alveolar rhabdomyosarcoma. Despite chemotherapy, patient succumbed to death after two months due to septic shock. Rhabdomyosarcoma is highly aggressive mesenchymal neoplasm which may present with diagnostic difficulty. This case highlights the importance of molecular studies in making an accurate diagnosis so that appropriate chemotherapy may be instituted.